2022
DOI: 10.1002/path.5920
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of the DNA methylome and transcriptome in uterine leiomyoma shows altered regulation of genes involved in metabolism, proliferation, extracellular matrix, and vesicles

Abstract: Uterine leiomyomas (ULs) are the most common benign tumors in women of reproductive age. Despite the high prevalence, tumor pathology remains unclear, which hampers the development of safe and effective treatments. Epigenetic mechanisms appear to be involved in UL development, particularly via DNA methylation that regulates gene expression. We aimed to determine the relationship between DNA methylation and gene expression in UL compared with adjacent myometrium (MM) to identify molecular mechanisms involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…To identify which DEGs could be implicated in UL pathogenesis, we integrated the transcriptomic data obtained by RNA-seq from two previous studies using independent patient cohorts [ 17 , 19 ]. The gene expression count matrix from the GSE192354 dataset revealed 1837 significant DEGs (FDR-adjusted p -value< 0.01) with a substantial difference in expression between ULs and MM tissue (log2FC > 1 or < − 1), including 1175 upregulated and 662 downregulated genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify which DEGs could be implicated in UL pathogenesis, we integrated the transcriptomic data obtained by RNA-seq from two previous studies using independent patient cohorts [ 17 , 19 ]. The gene expression count matrix from the GSE192354 dataset revealed 1837 significant DEGs (FDR-adjusted p -value< 0.01) with a substantial difference in expression between ULs and MM tissue (log2FC > 1 or < − 1), including 1175 upregulated and 662 downregulated genes.…”
Section: Resultsmentioning
confidence: 99%
“…The role of epigenomic instability, via aberrant DNA methylation, has been recently considered for the onset and maintenance of ULs [ 19 , 34 39 ]. Reversing the methylation could potentially restore gene expression and ultimately become a therapeutic alternative for women with ULs [ 19 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the well-studied epigenomic processes in mammals ( Bestor, 2000 ), DNA methylation was considered as a potential mechanism in the pathology of UFs. Many aberrantly hypermethylation/hypomethylation genes were detected in by genome-wide DNA methylation assays ( Li et al, 2003 ; Yamagata et al, 2009 ; Navarro et al, 2012 ; Islam et al, 2013 ; Maekawa et al, 2013 ; Carbajo-García et al, 2022 ), and numerous genes were validated to participate in the developmental progress of the UFs in vitro experiments. SATB homeobox 2 and neuregulin 1 were proved to be the upregulated hypermethylated genes involved in the pathogenesis of uterine leiomyoma by activating the WNT/β-catenin and TGF-β pathways ( Sato et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetics include variations in the gene expression profile not caused by changes in the DNA sequence, resulting from processes such as DNA methylation, histone modification, and non-coding RNAs [ 16 ]. Genome-wide DNA methylation studies have revealed subsets of suppressed or overexpressed genes accompanied by aberrant promoter methylation [ 17 , 18 , 19 ], also evaluating DNA methylation in UL focusing on stem cell population [ 20 ] or mutation status [ 21 ]. Furthermore, differential promoter access resulting from altered 3D chromatin structure and histone modifications plays a role in regulating transcription of key genes thought to be involved in leiomyoma etiology [ 22 ].…”
Section: Introductionmentioning
confidence: 99%